Hubungan Kecerdasan Emosional terhadap Hasil Belajar Anak Usia Dini - Anisa Nurdiyanti; Yuyun Yulianingsih; Syamiyah Syamiyah (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2018)
This study aims to determine the relationship of emotional intelligence in early childhood learning outcomes on aspects of emotional social development aged 5-6 years. This study uses quantitative correlational methods and approaches. The subject of this study was group B in one RA in Bandung City which amounted to 46 children. This study uses saturated samples, which means that all populations are sampled. Data collection techniques through observation sheets. The results of the analysis of research data using the calculation of the Spearman Rank correlation coefficient obtained a result of ρcount of 0.74. Meanwhile, the results of the calculation of the significance of the correlation test using t-test obtained the value of tcount of 7.33 and a significance level of 5% with db = 44 is 2.017. So, tcount = 7.33 > ttable = 2.017, and can be interpreted that there is a significant relationship between emotional intelligence and early childhood learning outcomes. In addition, the determination coefficient obtained is 55%. That is, emotional intelligence contributes as much as 55% of the results of early childhood learning in one RA in the city of Bandung. Keywords: early childhood, learning outcomes, emotional intelligence, development, social-emotional